Blood transfusion: is it safe for users? - Pusparini, Pusparini (Faculty of Medicine, Trisakti University, 2010)
Blood transfusion is a long-known life-saving procedure for patients in need of blood, as its history can be traced to about 200 years ago. The first successful blood transfusion performed from one human to another was pioneered by James Blundell, an obstetrician who in 1818 succeeded in transfusing 227 mL of blood to a patient with postpartum hemorrhage